2014
DOI: 10.4028/www.scientific.net/amm.706.128
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Load Occupancy Ratio on the Dynamic Response of an Elevator Car System

Abstract: In predictions of the dynamic behaviour of an elevator car system, it is important to take into account the influence of passengers’ behaviour in the car. In this paper a simulation model to analyse the influence of various loading car conditions on the dynamic response of the elevator system is developed. This involves the investigation of the dynamic response of the car with different loads. An experimental rig with a rectangular elevator platform fixed on the top of four silent blocks attached to a shaker i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Moreover, mathematical models to represent high rise elevators (Crespo et al, 2018;Fortgang et al, 2006), and specific parts of the elevator system such as the ropes (Kaczmarczyk et al, 2003) and the compensating sheave (Watanabe and Okawa, 2018) are found. The cabin has also been extensively studied because it is vulnerable to the vertical and the lateral vibrations that affect the passenger comfort (Coffen et al, 1997;Feng et al, 2009;Herrera et al, 2010Herrera et al, , 2014aQiu et al, 2020;Zhang and Yang, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, mathematical models to represent high rise elevators (Crespo et al, 2018;Fortgang et al, 2006), and specific parts of the elevator system such as the ropes (Kaczmarczyk et al, 2003) and the compensating sheave (Watanabe and Okawa, 2018) are found. The cabin has also been extensively studied because it is vulnerable to the vertical and the lateral vibrations that affect the passenger comfort (Coffen et al, 1997;Feng et al, 2009;Herrera et al, 2010Herrera et al, , 2014aQiu et al, 2020;Zhang and Yang, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, external variables may also influence the behavior of the system. Modeling and experimental testing of the influence of passengers were carried out by Herrera et al (2010Herrera et al ( , 2014aHerrera et al ( , 2014b and Kaczmarczyk et al (2003) studied the influence of the wind-induced building movement on the vibration of the ropes.…”
Section: Introductionmentioning
confidence: 99%
“…direct output feedback control algorithm. Herrera et al [4] considered the behavior of passengers in the car and established a model to analyze the influence of the car's dynamic characteristics under different loading conditions. Because the rolling guide shoe liners are made of rubber materials, its material properties give guide shoes nonlinear characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Since this system has ma, j a , 3 and l 4 a total of 12 random parameters, the mass matrix M, damping matrix C , and stiffness matrix K in the differential equations of motion also have randomness, and the following transformation is needed:…”
Section: High-speed Elevator Car System Dynamics Modelmentioning
confidence: 99%
“…Chang et al [2] established a four degree-of-freedom elevator system to study the excitation characteristics and the car dynamic response, and developed an active mass driver based on H ∞ direct output feedback control algorithm. Herrera et al [3] considered the behavior of passengers in the car and established a model to analyze the influence of the car dynamic characteristics under different loading conditions. However, for objective random excitation and random parameters of an elevator car, most literature did not consider or approximate the deterministic parameter.…”
Section: Introductionmentioning
confidence: 99%